NGHIÊN CỨU CHẾ TẠO VẬT LIỆU BLEND BA CẤU TỬ TRÊN CƠ SỞ CAO SU NITRIL BUTADIEN, CAO SU CLOPREN VÀ POLYVINYLCLORUA - Liên, Trần Kim; Tố Uyên, Đỗ Thị; Hải, Lương Như; Khải, Nguyễn Quang; Kháng, Đỗ Quang (Vietnam Journal of Chemistry, 2012)
Ternary blend material based on nitrile butadiene rubber (NBR), chloroprene rubber (NR) and polyvinyl chloride (PVC) was prepared by means of internal mixing method at 170oC with various ratios. The results showed that the optimal compatible ratio of blend (NBR/CR)/PVC is 80/20. At this ratio, blend material shows better smooth structure, physico-mechanical properties and thermal resistance than these of blend at other ratios.